Error Upper Bounds for a Computational Method for Nonlinear Boundary and Initial-Value Problems - Guimarães, Osvaldo; Piqueira, José Roberto Castilho (Mathematical Problems in Engineering, 2012)
This work develops a computational approach for boundary and initial-value problems by using operational matrices, in order to run an evolutive process in a Hilbert space. Besides, upper bounds for errors in the solutions and in their derivatives can be estimated providing accuracy measures.